The Role of Health Environment and Location in the Emergence of Urban Criminal Behaviours in Tehran - E Salehi (Tehran University of Medical Sciences, 2011)
Background: Although, the roots of criminal behaviours clearly lie in social, economic, and cultural factors, the increase criminal offences in urban settings has raised the issue of prevention through urban environmental health, planning and design. Methods: The approach of the study was based on the scientific research methodology and indicators were compiled from observations and comparative analyses of those urban spaces that are most often the sites of crime. Results: Pearson's correlation coefficient showed that 37% of sampled males and 51% of females emphasized on effectiveness of environmental factors. The urban space observations show that the environmental and physical factors affect on security and sensation of community safety among the citizens. Conclusion: Crime is committed in a particular place; place-related factors play a role in creating the potential for crimes to be committed. The results show the close bond between crimes and environmental problems.Recognition of the influence of location-specific characteristics and the correct environmental response may make it possible to prevent or at least reduce criminal acts in urban places.